(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1869)
Ralph Carr presents a letter he received from George Petrie that contained a transcription of some of the inscribed runes at Maes Howe. Carr highlights that the lighting conditions and faint inscription of these runes makes them very difficult to decipher. No translation of the runes is offered. Meeting notes for 10 May, 1869 are appended.